Efektivitas Pupuk NPK Majemuk dengan Pupuk Guano terhadap Pertumbuhan dan Produksi Tanaman Zucchini (Cucurbita pepo L.) - Mujaroah, Mujaroah; Amir, Nurbaiti; Astuti, Dessy Tri; Syafrullah, Syafrullah (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Mujaroah M, Amir N, Astuti DT, Syafrullah S. 2022. The effectiveness of compound npk fertilizer with guano fertilizer on the growth and production of zucchini (Cucurbita Pepo L.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 910-921. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Zucchini plants area annual plantas that area similar to pumpkins or eggplants whose fruit is harvested before ripe which belongs to the cucurbitaceae family. The purpose of this study was to determine and determine the effectiveness of Compound NPK Fertilizers and Guano Fertilizers which gave the best response to growth and increased production of zucchini (Cucurbita pepo L.) plants. The research has been carried out in one of the resident’s lands. Location in Perumnas Talang Kelapa Block 3 RT 61 NO. 41 RW 08 Alang-Alang Lebar Subdistrict, Palembang City, Sounth Sumatra in March until with May 2022. This study used a Split Plot Design with 9 treatment combinations which were repeated 3 times, resulting, in 27 treatment units with 3 sample plants. These are as follows: Main Plot For Compound NPK Fertilizer (N) consisting of 3 levels N1= 150 kg/ha, N2= 200 kg/ha, N3 = 250 kg/ha. Sub-plots for providing Guano Fertilizer (O)= terdin of 3 levels O1= 2,5 tons/ha, O2= 5 tons/ha, O3= 7,5 tons/ha. The variables observed were: plant height (cm), fruit diameter (cm), fruit length (cm), number of fruit per plot (fruit), fruit weight per plot (kg). The results showed that the treatment of compound NPK Fertilizer dosage of 250 kg/ha with Guano Fertilizer at a dose of 5 tons/ha gave the highest yield at fruit weight per plot 3,16 kg/plot or the equivalent of 6,32 tons/ha.